Environmental Disclosure as Corporate Social Responsibility: Evidence from the Biggest Nickel Mining in Indonesia - Murdifin, Imaduddin; Pelu, Muhammad Faisal AR; Putra, Aditya Aditya Halim Perdana Kusuma; Arumbarkah, A. Muara; Muslim, Muslim; Rahmah, Aulia (International Journal of Energy Economics and Policy, 2018)
The company’s business operations in Indonesia are very dependent on the company’s intention on the environment, especially mining companies. Mining companies are responsible not only for economic materiality aspects but also for environmental and social aspects for the sustainability of operations. In its interactions with the business and social environment, vulnerable mining companies are in the spotlight if they do not carry out disclosure of environmental responsibility proportionally in accordance with generally accepted standards. The purpose of this study is to qualitatively analyze the descriptive disclosure of Environmental Disclosure as a form of corporate social responsibility of PT. Vale as the largest Nickel mining company in Indonesia which also contributes number 2 nickel in the world. The results of this study state that environmental disclosure analysis of PT. Vale has not been fully optimized for all aspects of the surrounding community Keywords: Environmental Disclosure, Environmental Economics, Corporate Social Responsibility JEL Classifications: Q53, Q57 DOI: https://doi.org/10.32479/ijeep.7048